Resolution to Walls Surfaces Condensation & Mould Growth Issue in an 24-hours Air Conditioned Room - Ker, De Kuan; Ng, Samuel ShenqJye; Seow, Zhen Liang; Low, Shu Boey (2015)
Engineering Design Project is about enabling students to develop a set of skills in order to solve and complete an engineering problem. The whole process ¡s carried out on minimum supervision. There are a lot of factors in determining (he success of the project, this include time management, having a clear objective, proposing multiple solutions, understanding the obtained results and many more. By getting hold of the objectives and as well as outcomes, a clear path of direction can be obtained. Both the skill to work as an individual as well as the skill to work as a group is put at stake. With the combination of both, a well-structured and complete project can be the output.